A comparative workload-based methodology for performance evaluation of parallel computers - (:unkn) unknown (Elsevier, 1997)
A practical methodology for evaluating and comparing the performance of distributed memory Multiple Instruction Multiple Data (MIMD) systems is presented. The methodology determines machine parameters and program parameters separately, and predicts the performance of a given workload on the machines under consideration. Machine parameters are measured using benchmarks that consist of parallel algorithm structures. The methodology takes a workload-based approach in which a mix of application programs constitutes the workload. Performance of different systems are compared, under the given workload, using the ratio of their speeds. In order to validate the methodology, an example workload has been constructed and the time estimates have been compared with the actual runs, yielding good predicted values. Variations in the workload are analysed in terms of increase in problem sizes and changes in the frequency of particular algorithm groups. Utilization and scalability are used to compare the systems when the number of processors is increased. It has been shown that performance of parallel computers is sensitive to the changes in the workload and therefore any evaluation and comparison must consider a given user workload. Performance improvement that can be obtained by increasing the size of a distributed memory MIMD system depends on the characteristics of the workload as well as the parameters that characterize the communication speed of the parallel system.
Keywords: Code characterization; Execution time prediction; Machine characterization; MIMD performance; Parallel algorithms; Parallel computers; Performance evaluation; Performance prediction; Workload-based performance comparison